The effect of mental imagery training on self-confidence of sparring category pencak silat athletes - Hadian, Auttarky Manaf; Komarudin, Komarudin; Erawan, Bambang; Novian, Geraldi (Jurnal Patriot, 2025)
In the world of sports, psychological aspects cannot be separated from competition, there is a method that is often used in competitive sports that has been proven effective in increasing athlete self-confidence, namely mental imagery training because self-confidence is an important aspect in anything, especially for athletes in the pencak silat sport. This study aims to determine the significant effect of the Imagery training method on the self-confidence of pencak silat athletes in the trading category. The experimental method used in this study is a nonequivalent control group design involving 16 Pencak Silat Club Gerana athletes—sample selection using a purposive sampling technique. Treatment of 16 meetings to the sample intensively, before and after treatment the sample will be given the State Sport Confidence Inventory (SSCI) to measure self-confidence. After obtaining the data, it was analyzed using SPSS Version 26 using the t-test. The t value was 5.148 with a Sig value. (2-tailed) of 0.001 and the results for conventional training result t count of 3.479 with a Sig value. (2-tailed) of 0.010. Based on the test results, both treatments the Sig. (2-tailed) value of both treatments is <0.05 so that H0 is rejected. For the results of the Independent sample t-test which aims to determine the difference in the effect of different treatments, the Sig. (2-tailed) value is 0.001 <0.05. So it can be stated that there is a significant difference in the effect of mental imagery training with conventional training on the self-confidence of pencak silat athletes in the competing category. This study concludes that the imagery training method has a more significant effect than conventional training in the form of relaxation and is recommended to be applied to the pencak silat sport in the competing category because it has been proven to increase athlete self-confidence.